Campus Racial Incidents, Hate Crimes, and White Male and Female Students' Racial Attitudes. (2nd January 2020) - Garibay, Juan Carlos; Herrera, Felisha A.; Johnston-Guerrero, Marc P.; Garcia, Gina A.
ABSTRACT: Despite popular claims that the United States has reached a "post-racial" era—one in which race no longer matters for determining one's life chances—college students continue to have strong views toward whether or not racial discrimination is still a major problem in this country. Utilizing multilevel modeling on data merged from the Cooperative Institutional Research Program's (CIRP) 2005 Freshman Survey (TFS) and 2009 College Senior Survey (CSS), as well as the Integrated Postsecondary Educational Data System (IPEDS) and the Office of Postsecondary Education Campus Safety and Security database, this study examined individual and institutional predictors of white male and female college students' senior-year views on whether racial discrimination is still a major problem in the United States, with a particular focus on campus racially biased incidents and hate crimes. Results show that having a reported hate crime on campus did not have a significant association with white students' senior-year views, while a higher level of news coverage of campus racially biased incidents significantly predicted white women's senior-year views on racial discrimination. Implications of the findings with respect to higher education research, policy, and practice are discussed.